answersLogoWhite

0


Best Answer

x² + y² - 4x + y - 1 = 0

( x² - 4x ) + ( y² + y ) = 1

( x² - 4x + 4 ) + [ y² + y + (1/4) ] = 1 + 4 + (1/4)

( x - 2 )² + [ y + (1/2) ]² = [ √(21) / 2 ]²

This equation represents a Circle with

Centre ≡ ( 2, -1/2 ) and Radius = √(21) / 2.

________________________________________

Happy To Help !

________________________________________

User Avatar

Wiki User

12y ago
This answer is:
User Avatar

Add your answer:

Earn +20 pts
Q: What is the standard form of x2 plus y2-4x plus y-1 equals 0?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Continue Learning about Math & Arithmetic